Comparing stakeholder perspectives and biodiversity models in assessing scenarios of management change - Robin J. Pakeman; Alba Juárez-Bourke; Scott Herrett; Alice Hague; Anja Byg; Altea Lorenzo-Arribas; Anke Fischer; Laura MacLean; Keith Marshall; Gillian Donaldson-Selby; Alison J. Hester; Antonia Eastwood (Journal of Environmental Management, 2025)

An eight-founder wheat MAGIC population allows fine-mapping of flowering time loci and provides novel insights into the genetic control of flowering time - Laure Fourquet; Tobias Barber; Camila Campos-Mantello; Phil Howell; Beata Orman-Ligeza; Lawrence Percival-Alwyn; Gemma A. Rose; Hester Sheehan; Tally I. C. Wright; Friedrich Longin; Tobias Würschum; Dario Novoselovic; et al. (Theoretical and Applied Genetics, 2024)
Flowering time synchronizes reproductive development with favorable environmental conditions to optimize yield. Improved understanding of the genetic control of flowering will help optimize varietal adaptation to future agricultural systems under climate change. Here, we investigate the genetic basis of flowering time in winter wheat ( Triticum aestivum L.) using an eight-founder multi-parent advanced generation intercross (MAGIC) population. Flowering time data was collected from field trials across six growing seasons in the United Kingdom, followed by genetic analysis using a combination of linear modelling, simple interval mapping and composite interval mapping, using either single markers or founder haplotype probabilities. We detected 57 quantitative trait loci (QTL) across three growth stages linked to flowering time, of which 17 QTL were identified only when the major photoperiod response locus Ppd-D1 was included as a covariate. Of the 57 loci, ten were identified using all genetic mapping approaches and classified as ‘major’ QTL, including homoeologous loci on chromosomes 1B and 1D, and 4A and 4B. Additional Earliness per se flowering time QTL were identified, along with growth stage- and year-specific effects. Furthermore, six of the main-effect QTL were found to interact epistatically with Ppd-D1 . Finally, we exploited residual heterozygosity in the MAGIC recombinant inbred lines to Mendelize the Earliness per se QTL QFt.niab-5A.03 , which was confirmed to modulate flowering time by at least four days. This work provides detailed understanding of the genetic control of phenological variation within varieties relevant to the north-western European wheat genepool, aiding informed manipulation of flowering time in wheat breeding.

Factors affecting severity of wildfires in Scottish heathlands and blanket bogs - Noemi A.L. Naszarkowski; Thomas Cornulier; Sarah J. Woodin; Louise C. Ross; Alison J. Hester; Robin J. Pakeman (Science of The Total Environment, 2024)

Tree felling by beaver promotes regeneration in riparian woodlands whilst increasing resource availability for deer - Kelsey A. Wilson; Alan Law; Alison J. Hester; Martin J. Gaywood; Nigel J. Willby (Forest Ecology and Management, 2024)

Testing the response of northern white-cedar to simulated browsing: Evidence of apparent compensatory growth - Olivier Villemaire-Côté; Alison J. Hester; Jean-Pierre Tremblay; Jean-Claude Ruel (Forest Ecology and Management, 2023)

Mycena species can be opportunist‐generalist plant root invaders - Christoffer Bugge Harder; Emily Hesling; Synnøve S. Botnen; Kelsey E. Lorberau; Bálint Dima; Tea von Bonsdorff‐Salminen; Tuula Niskanen; Susan G. Jarvis; Andrew Ouimette; Alison Hester; Erik A. Hobbie; Andy F. S. Taylor; et al. (Environmental Microbiology, 2023)
Traditional strict separation of fungi into ecological niches as mutualist, parasite or saprotroph is increasingly called into question. Sequences of assumed saprotrophs have been amplified from plant root interiors, and several saprotrophic genera can invade and interact with host plants in laboratory growth experiments. However, it is uncertain if root invasion by saprotrophic fungi is a widespread phenomenon and if laboratory interactions mirror field conditions. Here, we focused on the widespread and speciose saprotrophic genus Mycena and performed (1) a systematic survey of their occurrences (in ITS1/ITS2 datasets) in mycorrhizal roots of 10 plant species, and (2) an analysis of natural abundances of 13 C/ 15 N stable isotope signatures of Mycena basidiocarps from five field locations to examine their trophic status. We found that Mycena was the only saprotrophic genus consistently found in 9 out of 10 plant host roots, with no indication that the host roots were senescent or otherwise vulnerable. Furthermore, Mycena basidiocarps displayed isotopic signatures consistent with published 13 C/ 15 N profiles of both saprotrophic and mutualistic lifestyles, supporting earlier laboratory‐based studies. We argue that Mycena are widespread latent invaders of healthy plant roots and that Mycena species may form a spectrum of interactions besides saprotrophy also in the field.

Tree planting in organic soils does not result in net carbon sequestration on decadal timescales - Nina L. Friggens; Alison J. Hester; Ruth J. Mitchell; Thomas C. Parker; Jens‐Arne Subke; Philip A. Wookey (Global Change Biology, 2020)
Tree planting is increasingly being proposed as a strategy to combat climate change through carbon (C) sequestration in tree biomass. However, total ecosystem C storage that includes soil organic C (SOC) must be considered to determine whether planting trees for climate change mitigation results in increased C storage. We show that planting two native tree species ( Betula pubescens and Pinus sylvestris ), of widespread Eurasian distribution, onto heather ( Calluna vulgaris ) moorland with podzolic and peaty podzolic soils in Scotland, did not lead to an increase in net ecosystem C stock 12 or 39 years after planting. Plots with trees had greater soil respiration and lower SOC in organic soil horizons than heather control plots. The decline in SOC cancelled out the increment in C stocks in tree biomass on decadal timescales. At all four experimental sites sampled, there was no net gain in ecosystem C stocks 12–39 years after afforestation—indeed we found a net ecosystem C loss in one of four sites with deciduous B. pubescens stands; no net gain in ecosystem C at three sites planted with B. pubescens ; and no net gain at additional stands of P. sylvestris . We hypothesize that altered mycorrhizal communities and autotrophic C inputs have led to positive ‘priming’ of soil organic matter, resulting in SOC loss, constraining the benefits of tree planting for ecosystem C sequestration. The results are of direct relevance to current policies, which promote tree planting on the assumption that this will increase net ecosystem C storage and contribute to climate change mitigation. Ecosystem‐level biogeochemistry and C fluxes must be better quantified and understood before we can be assured that large‐scale tree planting in regions with considerable pre‐existing SOC stocks will have the intended policy and climate change mitigation outcomes.

Knowledge sharing, problem solving and professional development in a Scottish Ecosystem Services Community of Practice - Marc J. Metzger; Jan Dick; Abi Gardner; Chloe Bellamy; Kirsty Blackstock; Calum Brown; Rachel Chisholm; Phoebe Cochrane; Joanna Drewitt; Alessandro Gimona; Alison Hester; Scot Mathieson; et al. (Regional Environmental Change, 2019)

Sheep grazing in the North Atlantic region: A long-term perspective on environmental sustainability - Louise C. Ross; Gunnar Austrheim; Leif-Jarle Asheim; Gunnar Bjarnason; Jon Feilberg; Anna Maria Fosaa; Alison J. Hester; Øystein Holand; Ingibjörg S. Jónsdóttir; Lis E. Mortensen; Atle Mysterud; Erla Olsen; et al. (Ambio, 2016)

How to Replicate the Functions and Biodiversity of a Threatened Tree Species? The Case of Fraxinus excelsior in Britain - Ruth J. Mitchell; Robin J. Pakeman; Alice Broome; Joan K. Beaton; Paul E. Bellamy; Rob W. Brooker; Chris J. Ellis; Alison J. Hester; Nick G. Hodgetts; Glenn R. Iason; Nick A. Littlewood; Gabor Pozsgai; et al. (Ecosystems, 2016)

Explaining the variation in the soil microbial community: do vegetation composition and soil chemistry explain the same or different parts of the microbial variation? - Ruth Joy Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2012)

Experimental evidence for herbivore limitation of the treeline - James D. M. Speed; Gunnar Austrheim; Alison J. Hester; Atle Mysterud (Ecology, 2010)
The treeline ecotone divides forest from open alpine or arctic vegetation states. Treelines are generally perceived to be temperature limited. The role of herbivores in limiting the treeline is more controversial, as experimental evidence from relevant large scales is lacking. Here we quantify the impact of different experimentally controlled herbivore densities on the recruitment and survival of birch Betula pubescens tortuosa along an altitudinal gradient in the mountains of southern Norway. After eight years of summer grazing in large‐scale enclosures at densities of 0, 25, and 80 sheep/km 2 , birch recruited within the whole altitudinal range of ungrazed enclosures, but recruitment was rarer in enclosures with low‐density sheep and was largely limited to within the treeline in enclosures with high‐density sheep. In contrast, the distribution of saplings (birch older than the experiment) did not differ between grazing treatments, suggesting that grazing sheep primarily limit the establishment of new tree recruits rather than decrease the survival of existing individuals. This study provides direct experimental evidence that herbivores can limit the treeline below its potential at the landscape scale and even at low herbivore densities in this climatic zone. Land use changes should thus be considered in addition to climatic changes as potential drivers of ecotone shifts.

Is vegetation composition or soil chemistry the best predictor of the soil microbial community? - Ruth J. Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2010)

Long-term impacts of goat browsing on bush-clump dynamics in a semi-arid subtropical savanna - Alison J. Hester; Peter F. Scogings; Winston S. W. Trollope (Plant Ecology, 2006)